The behavioral economics of dynamically inconsistent behavior: a critical assessment - Sebastian Krügel; Matthias Uhl (Social Choice and Welfare, 2023)
Preferences often change—even in short time intervals—due to either the mere passage of time (present-biased preferences) or changes in visceral or environmental conditions (state-dependent preferences). On the basis of empirical findings concerning state-dependent preferences, we critically discuss the "Aristotelian" view of unitary decision makers in economics. We illustrate that the conceptualization of preferences as "present-biased" as opposed to "state-dependent" has very different normative implications for which preferences should be considered "rational." Empirically, however, the two concepts are very difficult to distinguish. The economist can justify any paternalistic intervention if she can conceptualize changing preferences so flexibly, and she can easily become a benevolent despot. We therefore urge for a more careful "Heraclitean" view of decision-making that accepts that a person may consist of multiple selves.
Keywords: D01; D90; D91; 330